2006
DOI: 10.1371/journal.pbio.0040197
|View full text |Cite|
|
Sign up to set email alerts
|

Empirical Support for Optimal Virulence in a Castrating Parasite

Abstract: The trade-off hypothesis for the evolution of virulence predicts that parasite transmission stage production and host exploitation are balanced such that lifetime transmission success (LTS) is maximised. However, the experimental evidence for this prediction is weak, mainly because LTS, which indicates parasite fitness, has been difficult to measure. For castrating parasites, this simple model has been modified to take into account that parasites convert host reproductive resources into transmission stages. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
162
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(170 citation statements)
references
References 32 publications
8
162
0
Order By: Relevance
“…Indeed, the importance of the parasites' role has recently been emphasized by data presented (56) from the D. magna/P. ramosa system which identified the optimal model for parasite virulence as that in which the castrating parasite maximizes lifetime transmission success by converting host reproductive resources into transmission stages.…”
Section: Further Limitations-ignoring the Pathogensmentioning
confidence: 99%
“…Indeed, the importance of the parasites' role has recently been emphasized by data presented (56) from the D. magna/P. ramosa system which identified the optimal model for parasite virulence as that in which the castrating parasite maximizes lifetime transmission success by converting host reproductive resources into transmission stages.…”
Section: Further Limitations-ignoring the Pathogensmentioning
confidence: 99%
“…Avoiding either of these factors might provide the evolutionary pressure for tra repression. Furthermore, increased horizontal transfer might reduce vertical transmission by slowing host growth; such tradeoffs have been predicted and observed for diverse parasites (Bull et al, 1991;Kover et al, 1997;Kover and Clay, 1998;Messenger et al, 1999;Dahlberg and Chao, 2003;Jensen et al, 2006). Plasmids display a tradeoff between conjugation rate and vertical transfer (Turner et al, 1998;Turner, 2004), and have been shown to evolve reduced cost to the host at the expense of horizontal transfer when the environment limits conjugative spread (Dahlberg and Chao, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…First, we employ a clone of P. ramosa (single genotype), not field isolates. Field isolates may contain more than one parasite clone (Jensen et al, 2006;Mouton et al, 2007;Ben-Ami et al, 2008;Luijckx et al, 2011). The use of P. ramosa clones negates the complicating factors intrinsic to mixed infections and allows for a more definitive interpretation of experimental results .…”
Section: Introductionmentioning
confidence: 99%